Tunable Mixed-Mode Voltage Differencing Buffered Amplifier-Based Universal Filter with Independently High-Q Factor Controllability - Natchanai Roongmuanpha; Mohammad Faseehuddin; Norbert Herencsar; Worapong Tangsrirat (My University, 2021)
This paper proposes the design of a mixed-mode universal biquad configuration, which realizes generic filter functions in all four possible modes, namely voltage mode (VM), current mode (CM), transadmittance mode (TAM), and transimpedance mode (TIM). The filter architecture employs two voltage differencing buffered amplifiers (VDBAs), two resistors and two capacitors, and can provide lowpass (LP), bandpass (BP), highpass (HP), bandstop (BS), and allpass (AP) biquadratic filtering responses without any circuit alteration. All passive elements used are grounded, except VM. The circuit not only allows for the electronic tuning of the natural angular frequency (ωo), but also achieves orthogonal tunability of the quality factor (Q). It also provides the feature of availability of output voltage at the low-output impedance terminal in VM and TIM, and does not require inverting-type or double-type input signals to realize all the responses. Moreover, in all modes of operation, the high-Q filter can be easily obtained by adjusting a single resistance value. Influences of the VDBA nonidealities and parasitic elements are also discussed in detail. PSPICE simulations with TSMC 0.18-µm CMOS process parameters and experimental testing results with commercially available IC LT1228s have been used to validate the theoretical predictions.
Keywords: Digital biquad filter; All-pass filter; Analog and Mixed-Signal Circuit Design